Methotrexate improves the health-related quality of life of children with juvenile idiopathic arthritis. Issue 3 (17th September 2007) - Céspedes-Cruz, A; Gutiérrez-Suárez, R; Pistorio, A; Ravelli, A; Loy, A; Murray, K J; Gerloni, V; Wulffraat, N; Oliveira, S; Walsh, J; Calvo Penades, I; Alpigiani, M G; et al.
Abstract : Objectives: To examine the change in health-related quality of life (HRQOL) and its determinants in children with juvenile idiopathic arthritis (JIA) treated with methotrexate (MTX). Methods: Patients were extracted from the PRINTO clinical trial which aimed to evaluate the efficacy and safety profile of MTX administered in standard, intermediate or higher doses (10, 15 and 30 mg/m 2 /week respectively). Children with polyarticular-course JIA, who were less than 18 years and had a complete HRQOL assessment were included. Results: A total of 521 children were included. At baseline, patients with JIA showed poorer HRQOL (p<0.01) than healthy children. In 207/412 (50%) and 63 (15%) children, HRQOL values were 2 standard deviations below the mean of healthy controls in the physical and psychosocial summary scale, respectively. After 6 months of treatment with standard dose MTX, there was a statistically significant improvement in all HRQOL health concepts, particularly the physical ones. Similar improvements were observed in those who did not respond to a standard dose of MTX and were subsequently randomised to a higher dose. The presence of marked disability at baseline was associated with a fivefold increased risk of retaining poor physical health after 6 months of active treatment with standard dose MTX. Other less important determinants of retaining poor physical well-being were the baseline level of systemic inflammation, pain intensity and an antinuclear-antibody-negative status. Conclusions: MTX treatment produces a significant improvement across a wide range of HRQOL components, particularly in the physical domains, in patients with JIA.